The Effect of Learning Styles on the Performance of Architecture Students in Structural Design Courses - Erkan Yazıcı, Yasemin; YAZICI, GÖKHAN (Siyasal Kitabevi, Ankara, Turkey, 2011)
Every student has a prefered way of perceiving, interacting with, and responding to the learning environment. Instructors can use the information regarding the learning styles to shape their teaching approaches in order to enhance the performance of their students. This paper presents the findings of a study carried out at the Department of Architecture of Istanbul Kultur University to investigate the impact of learning styles on the performance of architecture students in structural design courses. Learning styles of 53 architecture students were assessed with the Kolb’s Learning Style Inventory (K-LSI). Academic performance of these students in mechanics and strength of materials courses were compared with their learning styles. It was observed that the academic performance of the students were consistent with their learning styles
Keywords: Learning Styles; Architectural Education; Structural Engineering Courses